Exploring At-Tafsir Al-Maudhu’i in the Malaysian context: a comprehensive analysis of Siddiq Fadzil's contributions - Zamziba, Muhammad Nur Farhan; Ali Yusuf, Imtiaz Ahmed Shaukat; H.Osman, Rahmad Ahmad; Rashid, Rabiatul Fatimah Azzahra (Global Academic Excellence, 2023)
This research will examine one of Malaysia's most contemporary schools of Islamic thought. This study revolves around the concept of At-Tafsir Al-Maudhu’i (thematic tafsir) which was propagated by Prof. Dato’ Dr. Siddiq Fadzil, the president of the Muslim Youth Movement of Malaysia (ABIM). In his numerous lectures, Siddiq Fadzil discussed this concept in about 80 lectures. The primary focus of his lectures was to elucidate how to interpret the Quran within the context and reality of Malaysia. Therefore, there are three conditions for interpreting At-Tafsir Al-Maudhu’i: First: The authentic text must be the Arabic classical tafsir. Second: A selective theme addressing current issues that have impacted the world, especially Malaysia, should be chosen. Third: Connecting and relating the tafsir to the Malaysian context is essential.